The Impact of Alphabet Inc.'S (Google) Services on the Advancement of Knowledge, Innovation and the Harnessing of Intellectual Capital in the Knowledge-Based Economy - Dorinela Nancu; Ana-Maria Barzecu (Ovidius University Annals: Economic Sciences Series, 2024)
We have chosen this theme because the knowledge-based economy is already the present, and the ICT sector is the optimal infrastructure for its development, so that knowledge, creativity and innovation, as well as intellectual capital, are accessible to all. In this context, we considered it necessary to analyze the extent to which individuals have been concerned to develop their knowledge, skills and creativity with the services of Alphabet Inc. (Google).